2015
DOI: 10.1093/ijnp/pyv112
|View full text |Cite
|
Sign up to set email alerts
|

3’-Deoxyadenosine (Cordycepin) Produces a Rapid and Robust Antidepressant Effect via Enhancing Prefrontal AMPA Receptor Signaling Pathway

Abstract: Background:The development of rapid and safe antidepressants for the treatment of major depression is in urgent demand. Converging evidence suggests that glutamatergic signaling seems to play important roles in the pathophysiology of depression.Methods:We studied the antidepressant effects of 3’-deoxyadenosine (3’-dA, Cordycepin) and the critical role of the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor in male CD-1 mice via behavioral and biochemical experiments. After 3’-dA treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…We found 10 papers indicating that cordycepin can have protective effects on the brain in various models of brain dysfunction. For instance, it reduces the effects of chronic unpredictable mild stress in animal models and improves depression-like behaviour [ 119 , 232 ]. Some studies have also shown that cordycepin ameliorates learning and memory deficits in ischemic animal models [ 233 , 234 , 235 , 236 ] and sleep disturbances [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found 10 papers indicating that cordycepin can have protective effects on the brain in various models of brain dysfunction. For instance, it reduces the effects of chronic unpredictable mild stress in animal models and improves depression-like behaviour [ 119 , 232 ]. Some studies have also shown that cordycepin ameliorates learning and memory deficits in ischemic animal models [ 233 , 234 , 235 , 236 ] and sleep disturbances [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lentinan is a polysaccharide isolated from the fruit body of Shiitake , and recently it has been reported that the antidepressant-like effects of lentinan were due to the enhanced prefrontal cortical expression of phosphorylation of AMPA GluR1 S845 and dendritic cell-associated C-type lectin-1 (Dectin-1), which is an immune regulator and receptor for lentinan [ 104 ]. 3’-Deoxyadenosine (3’-dA, Cordycepin), one of the major bioactive metabolites in the Cordyceps militaris , was identified to produce the rapid antidepressant effects by enhancing GluR1 S845 phosphorylation in the prefrontal cortex and hippocampus, and cordycepin modulates GluR1 synaptic localization in a subtype-specific and brain region-specific manner [ 105 ].…”
Section: Regulation Of Glutamate-mediated Signaling By the Natural Comentioning
confidence: 99%
“…Treatment with the antidepressant imipramine blocked social avoidance behavior and reduced microglia IL-6 in animals exposed to stress or those given a systemic injection of LPS (Ramirez et al., 2015). Increased IL-6 protein was reported in the hippocampus of rats that underwent chronic unpredictable stress (Tianzhu et al., 2014) and was attenuated by chronic treatment with the antidepressant fluoxetine or treatment with an alternative medicine Cordycepin, a derivative of adenosine extracted from fungi shown to have antidepressant efficacy (Li et al., 2015). Within the prefrontal cortex, increased levels of IL-6 protein were reported in rats exposed to uncontrollable shock that demonstrated LH behavior, but not in animals that were resilient to the same stressor (Sukoff Rizzo et al., 2012).…”
Section: Central Il-6 Contributes To Stress Sensitivitymentioning
confidence: 99%